Immune signatures predicting the clinical outcome of peanut oral immunotherapy: where we stand - Wanniang, Naphisabet; Boehm, Theresa-Maria; Codreanu-Morel, Françoise; Divaret-Chauveau, Amandine; Assugeni, Isabela; Hilger, Christiane; Kuehn, Annette (Frontiers in Allergy, 2023)
Peanut allergy is a growing health concern that can cause mild to severe anaphylaxis as well as reduced quality of life in patients and their families. Oral immunotherapy is an important therapeutic intervention that aims to reshape the immune system toward a higher threshold dose reactivity and sustained unresponsiveness in some patients. From an immunological point of view, young patients, especially those under 3 years old, seem to have the best chance for therapy success. To date, surrogate markers for therapy duration and response are evasive. We provide a comprehensive overview of the current literature state regarding immune signatures evolving over the course of oral immunotherapy as well as baseline immune conditions prior to the initiation of treatment. Although research comparing clinical and immune traits in the first years of life vs. later stages across different age groups is limited, promising insights are available on immunological endotypes among peanut-allergic patients. The available data call for continued research to fill in gaps in knowledge, possibly in an integrated manner, to design novel precision health approaches for advanced therapeutic interventions in peanut allergy.